Energy Efficient Design for Two-Way AF Relay Networks - Yong Li; Zhengguang Zheng; Mingyue Zhao; Yunli Chen; Chuanyong Liu (International Journal of Antennas and Propagation)
Conventional designs on two-way relay networks mainly focus on the spectral efficiency (SE) rather than energy efficiency (EE). In this paper, we consider a system where two source nodes communicate with each other via an amplify-and-forward (AF) relay node and study the power allocation schemes to maximize EE while ensuring a certain data rate. We propose an optimal energy-efficient power allocation algorithm based on iterative search technique. In addition, a closed-form suboptimal solution is derived with reduced complexity and negligible performance degradation. Numerical results show that the proposed schemes can achieve considerable EE improvement compared with conventional designs.